The Effectiveness of Implementing the Digital-Based Educational Control Information System (SI-KEPPO) to Improve Follow-Up Visit Compliance among Patients with Diabetes Mellitus: Penerapan Inovasi SI-KEPPO Berbasis Digital untuk Meningkatkan Kepatuhan Kontrol Pasien Diabetes Melitus - Linda, Baiq Linda Agustina; Mardiati, Mardiati; Yulia, Yulia Misni; Noor Ika Wardani; Dodi, Dodi Wijaya; Rondhianto, Rondhianto (Journal of Community Empowerment for Multidisciplinary (JCEMTY), 2025)
Diabetes Mellitus (DM) is a chronic disease that requires long-term and consistent monitoring to prevent complications. However, low adherence to follow-up visits remains a significant challenge in primary healthcare settings, including at Cakranegara Public Health Center in Mataram City. Based on data from January to May 2025, only 62.6% of the total 957 DM patients returned for scheduled follow-up visits. This community service initiative aimed to implement and analyze the effectiveness of a digital innovation, SI-KEPPO (Educational Control Information System), in improving follow-up adherence among DM patients. The methods included needs assessment and the development of an Android-based SI-KEPPO application. Evaluation was conducted through observations and interviews with program officers and patients. The results demonstrated improved follow-up compliance during the 4-day trial period. Patients reported that the application made it easier to remember visit schedules and made them feel more cared for through regularly delivered educational messages. The SI-KEPPO application also enhanced family involvement in patient support and facilitated monitoring of non-compliant patients by program officers. In conclusion, the implementation of the SI-KEPPO innovation effectively increased follow-up visit adherence among DM patients, strengthened digital approaches in community health services, and is recommended for integration into the Prolanis management system at the primary healthcare level.